2022
DOI: 10.3389/fimmu.2022.872170
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of the Prognosis and Biological Function for TRPV Channel Family in Clear Cell Renal Cell Carcinoma

Abstract: BackgroundThe transient receptor potential vanilloid (TRPV) channels family, TRPV1-6, has been identified to profoundly affect a wide spectrum of pathological processes in various cancers. However, the biological function and prognostic value of TRPVs in clear cell renal cell carcinoma (ccRCC) are still largely unknown.MethodsWe obtained the gene expression data and clinical information of 539 ccRCC patients from The Cancer Genome Atlas (TCGA) database. A series of databases were used for data processing and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Fifth, there is also a significant correlation between TRPV in bladder cancer immune infiltration and tumor microenvironment, suggesting that it can predict the effect of immunotherapy. Studies have shown that TRPV affects immune infiltration and prognosis of renal cell carcinoma [ 28 ]. In addition, we also analyzed TRPV mutation and copy number variants in bladder cancer and found that various types of copy number variants were associated with decreased immune cell content.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, there is also a significant correlation between TRPV in bladder cancer immune infiltration and tumor microenvironment, suggesting that it can predict the effect of immunotherapy. Studies have shown that TRPV affects immune infiltration and prognosis of renal cell carcinoma [ 28 ]. In addition, we also analyzed TRPV mutation and copy number variants in bladder cancer and found that various types of copy number variants were associated with decreased immune cell content.…”
Section: Discussionmentioning
confidence: 99%
“…We applied the GeneMANIA online database 3 to predict co-DEGs’ PPI network ( Warde-Farley et al, 2010 ). It is an online analysis tool that widely used to demonstrate and evaluate gene interactions ( Jiang et al, 2022 ; Tian et al, 2022 ). Given a query list of genes, GeneMANIA will find more genes like those.…”
Section: Methodsmentioning
confidence: 99%
“…TRPV3 mainly exists in sensory nerve cells and skin keratinocytes in the human body and senses temperature stimuli by forming a complex with TRPV1(28). Studies have shown that in renal clear cell carcinoma and non-small cell lung cancer, the high expression of TRPV3 is signi cantly correlated with increased tumor grade and poor prognosis, and it affects the accumulation of T cells in various tumor immune microenvironments, which is related to tumor immune in ltration (29,30). Our analysis of singlecell data found that in malignant cells, oligodendrocytes, and endothelial cells, it was expressed in various cells, such as monocytes and macrophages, and may play a complex regulatory role.…”
Section: Discussionmentioning
confidence: 99%